GE_GERICHTE P/3756/2016 vom 4. Juli 2018 - GE Cour de justice (2018)
ABUS D'AUTORITÉ ; LÉSION CORPORELLE SIMPLE ; CLASSEMENT DE LA PROCÉDURE ; EXCUSABILITÉ ; ASSISTANCE JUDICIAIRE | CP.312; CP.123; CP.125; CP.319; CP.14; CPP.136; LPol.45